Globalization and Environmental Sustainability in Contemporary Ceramics (Iraq as a Model) (Al-Academy, 2025)
The removal of barriers between countries has significantly altered the intellectual structure of the individual and, consequently, the collective. These barriers can only be removed through the presence of ethereal means of communication.This change has served the interests of thought, which has gradually evolved to possess sufficient awareness to rely on rational judgment to devise mechanisms for adapting to the surrounding environment. This awareness is achieved by processing information obtained through the senses to arrive at realistic and logical conclusions that are appropriate for the era in which we live.The research problem is summarized in the following question: What are the manifestations of the impact of globalization on the environmental sustainability of contemporary ethnic ceramic art? The first chapter was concerned with globalization, its history and how it works. The second chapter moved to environmental awareness and sustainability, its nature and how it was affected by the radical changes of globalization and its impact on environmental sustainability in its cultural, intellectual and ideological forms. The third chapter focused on the specialty and presented an introduction to contemporary ceramics, the mechanism of its development and the extent to which the Iraqi artistic product was affected by the occurring change. These discussions resulted in five indicators that were a reference for analyzing the samples. The third chapter dealt with four samples that represented the research community and were analyzed using the descriptive analytical method. The most important results of the analysis were that the artist deliberately sheds his identity and self partially and reformulates it in a contemporary style and employs it in forms with different connotations, i.e. representing everyone through the singular in a way that suits the principles of sustainability to preserve the local environment